2014
DOI: 10.1007/s00253-014-6201-x
|View full text |Cite
|
Sign up to set email alerts
|

α-N-Acetylglucosaminidase from Bifidobacterium bifidum specifically hydrolyzes α-linked N-acetylglucosamine at nonreducing terminus of O-glycan on gastric mucin

Abstract: α-Linked N-acetylglucosamine is one of the major glyco-epitopes in O-glycan of gastroduodenal mucin. Here, we identified glycoside hydrolase (GH) family 89 α-N-acetylglucosaminidase, termed AgnB, from Bifidobacterium bifidum JCM 1254, which is essentially specific to GlcNAcα1-4Gal structure. AgnB is a membrane-anchored extracellular enzyme consisting of a GH89 domain and four carbohydrate-binding module (CBM) 32 domains. Among four CBM32 domains, three tandem ones at C-terminus showed to bind porcine gastric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…The reports on a GH95 1,2-α-l-fucosidase (AfcA) from B. bifidum JCM 1254 by Katayama et al [56] and a galactose operon containing a gene encoding a GH112 galacto-N-biose (GNB)/LNB phosphorylase from B. longum JCM 1217 by Kitaoka et al [57] were the key findings that revived attention on HMOs by linking them to bifidobacterial biology, long after the first notion, proposed in 1954 by Gauhe et al [58], that milk oligosaccharides serve as a bifidus factor. Since then, using the strain B. bifidum JCM 1254, extensive studies have been carried out and the gene products relevant to the HMO/mucin utilization pathways have been successfully isolated and characterized [26,27,[59][60][61][62][63][64][65][66]. These efforts have illustrated how B. bifidum extracellularly degrades HMOs and mucin O-glycans into smaller sugars by the concerted action of the many cell surface-anchored GHs summarized in Figure 1.…”
Section: Glycoside Hydrolases Involved In the Degradation Of Hmos/mucmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports on a GH95 1,2-α-l-fucosidase (AfcA) from B. bifidum JCM 1254 by Katayama et al [56] and a galactose operon containing a gene encoding a GH112 galacto-N-biose (GNB)/LNB phosphorylase from B. longum JCM 1217 by Kitaoka et al [57] were the key findings that revived attention on HMOs by linking them to bifidobacterial biology, long after the first notion, proposed in 1954 by Gauhe et al [58], that milk oligosaccharides serve as a bifidus factor. Since then, using the strain B. bifidum JCM 1254, extensive studies have been carried out and the gene products relevant to the HMO/mucin utilization pathways have been successfully isolated and characterized [26,27,[59][60][61][62][63][64][65][66]. These efforts have illustrated how B. bifidum extracellularly degrades HMOs and mucin O-glycans into smaller sugars by the concerted action of the many cell surface-anchored GHs summarized in Figure 1.…”
Section: Glycoside Hydrolases Involved In the Degradation Of Hmos/mucmentioning
confidence: 99%
“…Furthermore, B. bifidum possesses specific GHs for degrading various glycan epitopes that are frequently found on mucin O-glycans. GH89 α-N-acetylglucosaminidase acts on terminal α-linked GlcNAc linkages attached to gastric mucin O-glycans [59], while GH110 α-galactosidase acts on the blood group antigen B to liberate Gal [64]. Interestingly, B. bifidum does not have a gene encoding GH109 α-N-acetylgalactosaminidase that acts on the blood group antigen A [69].…”
Section: Glycoside Hydrolases Involved In the Degradation Of Hmos/mucmentioning
confidence: 99%
“…The expression of both genes was highly induced in the presence of mucin ( Ruas-Madiedo et al, 2008 ). Moreover, two novel α- N -acetylgalactosaminidases from B. bifidum JCM 1254 have been identified, NagBb ( Kiyohara et al, 2012 ) and AgnB ( Shimada et al, 2014 ). These enzymes exhibit activity against the core structures in mucin O-glycans.…”
Section: Discovering Probiotics With Genetics and Omicsmentioning
confidence: 99%
“…infantis, and B. longum subsp. longum-utilize oligosaccharides from breast milk (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and glycoprotein glycans secreted from the gastrointestinal tract (19)(20)(21)(22). We also reported that B. longum subsp.…”
mentioning
confidence: 89%